Selective Dissociation of C4F9 COI Molecules by the Second-Harmonic Radiation of Pulsed TEA CO2 Laser. Issue 3 (1992) - Bildinov, I. K.; Laptev, V. B.; Ryabov, E. A.; Tumanova, L. M.
Abstract : IR multiphoton dissociation of C4 F9 COI was studied by the second-harmonic radiation of TEA CO2 laser. The stretching vibration of the carbonyl bondν C = O was excited. The second harmonic of CO2 laser was generated with the use of nonlinear crystal AgGaSe2 . The maximum energy fluence at focus was Φ ≃ 1.2 J/cm 2 . The MPD of C4 F9 COI was proved to be effective and selective with respect to oxygen and carbon isotopes. The main dissociation products were C4 F9 I and CO. The dissociation product, CO, was enriched with both 16 O and 12 C when the C4 F9 COI molecule was excited at the center of the bandν C = O by the laser line 10P (18) with 2 ω las = 1797.2 cm −1 . The maximum selectivities measured for oxygen and carbon wereα (16/18) = 20 andα (12/13) = 25 respectively.